Cell and Gene Therapy: The Present and Future of Medicine - Iftikhar, Raheel (Pakistan Armed Forces Medical Journal, 2024)
The 21st century has seen rapid advancements in the diagnosis and treatment of cancer and immune dysfunction diseases. The first step involves the diagnosis and risk stratification of solid organ cancers, haematological malignancies, and disorders of the immune system, which frequently require genetic testing. This genetic diagnosis paves the way for treatment of these disorders, which are fatal or associated with significant disability if left untreated. Recent progress in our knowledge of these genetic pathways has led to the creation of state-of-the-art treatments, such as CAR-T cells,1 mesenchymal